The Effect of Passion for Outdoor Activities on Employee Well-Being Using Nature Connectedness as the Mediating Variable and Environmental Identity as the Moderating Variable - Zhang C; Ma X; Liu L (Psychology Research and Behavior Management, 2023)
Chunyu Zhang, Xiao Ma, Liping Liu School of Economics and Management, Guangxi Normal University, Guilin, 541006, People’s Republic of ChinaCorrespondence: Xiao Ma; Liping Liu, School of Economics and Management, Guangxi Normal University, No. 1 Yanzhong Road, Yanshan District, Guilin, 541006, People’s Republic of China, Email mxsawyer@163.com; 865248131@qq.comPurpose: Although prior research has found outdoor activities to be an important effect on employee well-being, the mechanisms of their effect are understudied. This study integrated the Broaden-and-Build Theory, Attention Restoration Theory and Cognitive Assessment Theory to examine the relation between passion for outdoor activities (two dimensions, namely, harmonious passion, obsessive passion) and employee well-being (three dimensions, namely, life well-being, workplace well-being, psychological well-being) by the mediating role of nature connectedness and the moderating role of environmental identity.Participants and Methods: Data were collected from 403 employees of Guangxi enterprises in China. The structural equation model was constructed using AMOS and SmartPLS to test the hypotheses proposed in this study.Results: Our results confirm that harmonious passion for outdoor activities had a positive effect on employee nature connectedness, workplace well-being and psychological well-being. Obsessive passion for outdoor activities had a negative effect on employee nature connectedness, life well-being and psychological well-being. Natural connectedness has a positive effect on all three dimensions of employee well-being. Nature connectedness mediates between harmonious passion for outdoor activities and all three dimensions of employee well-being. Environmental identity positively moderated the relationship between nature connectedness and the three dimensions of employee well-being. Harmonious passion for outdoor activities has no direct effect on employee life well-being. Obsessive passion for outdoor activities had no direct effect on employee workplace well-being.Conclusion: This study reveals the mechanism of passion for outdoor activities on employee well-being from a new perspective and unveils that the two dimensions of passion for outdoor activities have different effects on employees’ life well-being, workplace well-being, and psychological well-being. Business managers should give attention to the benefits of outdoor activities and nature connectedness for their employees, through which they can relieve stress at work, recover attention and improve well-being.Keywords: Passion for Outdoor Activities, Employee Well-being, Broaden-and-Build Theory, Attention Restoration Theory, Cognitive Assessment Theory